Hubungan Faktor Demografi dengan Pengetahuan Cara Penggunaan Obat Bebas dan Bebas Terbatas di Kelurahan Penggilingan - Charles; Meiana Dwi Andini; Guruh Subagya (Jurnal Farmasi IKIFA, 2023)
Various health problems, especially those related to drugs, are still found in society. Starting from wrong use, drug abuse, the occurrence of drug side effects from the mildest to fatal. In order to avoid these negative impacts, it is necessary to provide adequate information to the public regarding how to obtain medicines correctly, use medicines correctly, store medicines correctly, and dispose of medicines correctly. Correct use of drugs will increase the success of therapy, incorrect use will increase therapy failure. People's efforts to treat themselves are known as self-medication. Self-medication can be a source of medication errors due to limited public knowledge of drugs and their use. The aim of this research is to determine the relationship between demographic factors and knowledge of how to use over-the-counter drugs and limited over-the-counter drugs in the community in Palasan Village, East Jakarta. This research is a non-experimental research with a total of 196 respondents. This research method is quantitative research. Based on the research results, it is known that overall 110 respondents (56%) had sufficient knowledge regarding the use of free and over-the-counter medicines, 64 respondents (33%) had good knowledge and 22 respondents (11%) had poor knowledge. Statistical tests show that there is no relationship between demographics and limited knowledge of how to use over-the-counter and over-the-counter drugs in the Pisiran sub-district, East Jakarta